Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of pediatric nephrectomy and partial nephrectomy - Salvatore Fabio Chiarenza; Cosimo Bleve; Ciro Esposito; Maria Escolino; Fabio Beretta; Maurizio Cheli; Vincenzo Di Benedetto; Maria Grazia Scuderi; Giovanni Casadio; Maurizio Marzaro; Leon Francesco Fascetti; Pietro Bagolan; et al. (PAGEPress Publications, 2019)
Throughout history, the pediatric laparoscopic nephrectomy was first described at the beginning of the Nineties by Erlich and colleagues in a child and by Koyle and colleagues in an unweaned patient. (...)